DISTINGSI TIPOLOGI KURIKULUM MERDEKA BELAJAR DENGAN METODE MERFDEKA BELAJAR RASULULLAH SAW - Muhammad Sabri; Ilham Syukri (Program Studi Manajemen Pendidikan Islam, 2023)
This study aims to explore the typology of independent learning at the time of the Prophet with an independent learning curriculum. The method in this study is descriptive qualitative with a library research approach. That is, this research is based on literature studies and not field studies. The sources of data in this study are related hadiths, and hadith themes related to education originating from hadith books, articles, papers and existing articles. Sources of data were obtained from original books of hadith which were searched manually, and using shof hadith, google book, google sholar and existing webseit. As for data analysis techniques, namely, data is collected, read, analyzed, and conclusions are drawn so as to find new information from research results. The results of the findings are that Merdeka learning at the time of the Prophet Muhammad SAW was carried out by people who were capable, skilled, intelligent and had high knowledge. While learning independence at this time only does not look at professionalism, instead existing students have the right to get independent learning. Furthermore, the conclusion of the truth from independent learning at the time of the Prophet was based on the Prophet Muhammad SAW. That is, the more progressive thinking in determining policies about something, still the words of the Messenger of Allah are true statements. Meanwhile, independent study in the Indonesian context, the truth of something from research results from students depends on the students after carrying out scientific research testing